2015
DOI: 10.1523/jneurosci.0214-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

A 3.7 kb Fragment of the MouseScn10aGene Promoter Directs Neural Crest But Not Placodal Lineage EGFP Expression in a Transgenic Animal

Abstract: Under physiological conditions, the voltage-gated sodium channel Na v 1.8 is expressed almost exclusively in primary sensory neurons. The mechanism restricting Na v 1.8 expression is not entirely clear, but we have previously described a 3.7 kb fragment of the Scn10a promoter capable of recapitulating the tissue-specific expression of Na v 1.8 in transfected neurons and cell lines (Puhl and Ikeda, 2008). To validate these studies in vivo, a transgenic mouse encoding EGFP under the control of this putative sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The possible existence of TTX-resistant sodium channels (Na v 1.5, Na v 1.8 and Na v 1.9) 48 might also be taken into consideration. Among these channels, Na v 1.8 is reported to be expressed in the PVN; however, its sodium channel current ( I Na ) accounts for less than 2% of the total I Na 49 . In addition, we sequentially screened multiple substances; however, GPCR itself can be modulated by specific substances via some mechanisms, such as desensitization/resensitization 50 and heterodimerization 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The possible existence of TTX-resistant sodium channels (Na v 1.5, Na v 1.8 and Na v 1.9) 48 might also be taken into consideration. Among these channels, Na v 1.8 is reported to be expressed in the PVN; however, its sodium channel current ( I Na ) accounts for less than 2% of the total I Na 49 . In addition, we sequentially screened multiple substances; however, GPCR itself can be modulated by specific substances via some mechanisms, such as desensitization/resensitization 50 and heterodimerization 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory dysregulation of other molecules may have occurred during development, for example, the TTX-S current was up-regulated in Na V 1.8-null mutant mice 6 , and Na V 1.7 knockout was reported to increase met-enkephalin expression 49 . Additionally, Na V 1.8 expression has been reported in CNS nuclei of naïve mice 50 , thus Na V 1.8-Cre driven Na V 1.6 knockout in these neurons may confound the effects of Na V 1.6 deletion in primary afferents. Moreover, normal neuropathic pain has also been reported to be retained following Na V 1.8 knockout, Na V 1.7/Na V 1.8 double knockout or genetic ablation of Na V 1.8-positive neurons 5 , 6 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Voltage-gated sodium channels, such as Na v 1.7, are expressed in the brain including in neurons involved in energy balance [46] . One study reported widespread expression for Na v 1.8 in the mouse brain including the hypothalamus [47] . However, we have examined the brain of Na v 1.8-Cre-tdTomato reporter mice and found no evidence of any Cre activity in the hypothalamus (not shown).…”
Section: Discussionmentioning
confidence: 99%